Maskless Fabrication of Aluminum Nanoparticles for Plasmonic Enhancement of Lead Halide Perovskite Lasers. Issue 21 (25th August 2017) - Wang, Shuai; Fang, Jimao; Zhang, Chen; Sun, Shang; Wang, Kaiyang; Xiao, Shumin; Song, Qinghai
Abstract: Lead halide perovskite microlasers have been intensively studied in the past few years. While a number of unique laser properties have been demonstrated, the main laser characteristics are determined by the crystal quality and the shapes of synthesized materials. Patterning the semiconductors with plasmonic nanostructures is an effective way to control light emission and absorption. However, due to the instability of perovskites, most of nanofabrication technologies of plasmonic nanostructures will significantly spoil the qualities of perovskite devices. Here the surface plasmon enhanced laser emissions from all‐inorganic lead halide perovskites are experimentally demonstrated. Without using any mask or expensive pattern generations, relatively uniform aluminum nanoparticles (NPs) are deposited onto the top surface of CsPbBr3 perovskites with electron beam evaporation. After the deposition of optimized aluminum NPs, the thresholds of whispering‐gallery‐mode lasers in CsPbBr3 perovskite microrods are significantly reduced by more than 20% and the output intensities of perovskite microlasers are significantly enhanced by more than an order of magnitude via the plasmonic resonances. Considering the simple, controllable, and cost‐effective fabrication process, this research shall route a new avenue to the control of perovskite microlasers and their applications. Abstract : Relatively uniform aluminum nanoparticles (NPs) are deposited onto the top surface of CsPbBr3 perovskites with electron beam evaporation. Due to these optimized aluminum NPs, the thresholds of whispering‐gallery‐mode lasers in microrods are significantly reduced by more than 20% and the output intensities of perovskite microlasers are enhanced by more than an order of magnitude via the plasmonic resonances.